The effects of mindfulness-based interventions on alleviating academic burnout in medical students: a systematic review and meta-analysis - Zhizhuo Wang; Peiyun Wu; Yutong Hou; Jing Guo; Cheng Lin (BMC, 2024)
Abstract Background Mindfulness-based interventions have been tested to be the effective approach for preventing/reducing burnout in medical students. Therefore, this systematic review and meta-analysis aimed to synthesize the scientific evidence and quantify the pooled effect of MBIs on the burnout syndrome in medical students. Methods A comprehensive literature search was conducted in the databases, including PubMed, Embase, ERIC, PsycINFO, Scopus, Cochrane Central Register of Controlled Trials (CENTRAL), China National knowledge Information Database (CNKI) and WanFang Database from database inception to February 2023 using the terms of "mindfulness", "burnout" and "medical students". Two reviewers independently reviewed the studies, and extracted the data of the eligible studies, as well as assessed the risk of bias. A random-effects model was employed to calculate the standardized mean differences (SMD) with 95% confidence intervals (CI) of overall burnout and its sub-domains of burnout (i.e., emotional exhaustion, cynicism, and academic efficacy). Results Of 316 records in total, nine studies (with 810 medical students) were ultimately included. The four RCT studies demonstrated an overall judgment of some concerns risk of bias, and the overall risk of biases of the five qRCT studies were judged as serious. In term of the SORT, the RCT and qRCT studies were evaluated as level 2 evidence, and the overall strength of recommendation was classified as B (limited-quality patient-oriented evidence). The pooled analysis showed that MBIs were associated with significant small to moderate improvements for medical students' overall burnout (SMD=-0.64; 95% CI [-1.12, -0.16]; P = 0.009) in the included four RCTs, emotional exhaustion (SMD=-0.27; 95% CI [-0.50, -0.03]; P = 0.03) and academic efficacy (SMD = 0.43; 95% CI [0.20, 0.66]; P<0.001) in the four qRCTs. Conclusions MBIs can serve as an effective approach for reducing burnout symptoms in medical students. Future high-quality studies with a larger sample size and robust randomized controlled trial methodologies should be obtained to reinforce the effectiveness of MBIs for reducing academic burnout in medical students.